1991
DOI: 10.1016/s0022-5347(17)38508-7
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Prostate Volume by Transrectal Ultrasound

Abstract: Estimation of prostate gland volume with transrectal ultrasound may provide important information in the evaluation of benign and malignant prostatic diseases. To determine the most accurate means of volume estimation 150 patients underwent transrectal ultrasound with 15 separate methods of volume estimation. All patients underwent subsequent radical prostatectomy or cystoprostatectomy. Prostate specimen weights were compared with the results of each volume estimation method. Step-section planimetry, previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
251
3
2

Year Published

1993
1993
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 480 publications
(264 citation statements)
references
References 19 publications
8
251
3
2
Order By: Relevance
“…However, this method does not necessarily determine the true in vivo prostate volume, due to shrinkage because of loss of blood supply, 5 and the volume might also be overestimated because of adjacent periprostatic tissue. 13 Several methodological studies, like measurement of water filled balloons, 14 and cadaver studies 13,15 have demonstrated that under ideal conditions, planimetry measures a volume very close to the true volume, and can be used as the gold standard of prostate volume measurement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this method does not necessarily determine the true in vivo prostate volume, due to shrinkage because of loss of blood supply, 5 and the volume might also be overestimated because of adjacent periprostatic tissue. 13 Several methodological studies, like measurement of water filled balloons, 14 and cadaver studies 13,15 have demonstrated that under ideal conditions, planimetry measures a volume very close to the true volume, and can be used as the gold standard of prostate volume measurement.…”
Section: Discussionmentioning
confidence: 99%
“…The prolate elipsoid formula, multiplying the largest anterioposterior (height), transverse (width) and cephalocaudal (length) prostate diameters by 0.524 (H6W6L6p/6) is probably the most commonly used method, 6,7 since it is rapid, reproducible, and has been shown to have high correlation with the actual prostate volume. 5 However, it has been questioned whether the prolate elipsoid formula gives accurate results in large prostates. 5,8 The prolate spheroid formula W6W6H6p/6 might be equally accurate, 5 and has the advantage of requiring measurements in the transversal plane only.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These investigators were all carefully trained in a standardized method of assessing prostate volume by TRUS. 7 Each took part in a 1-h lecture explaining the techniques of measurement of the prostate; the instruction included a teaching videotape as well as printed materials explaining the specific techniques to be utilized. The investigators were also given a copy of the videotape and asked to review it immediately prior to performing each examination.…”
Section: Methodsmentioning
confidence: 99%
“…7 Statistical analyses and graphing were performed using SigmaStat and SigmaPlot as well as SPSS vs 11.0. Baseline data distributions were described by mean and standard deviation.…”
Section: Methodsmentioning
confidence: 99%